A Conservation Hatchery Population of Delta Smelt Shows Evidence of Genetic Adaptation to Captivity After 9 Generations. (17th July 2018) - Finger, Amanda J; Mahardja, Brian; Fisch, Kathleen M; Benjamin, Alyssa; Lindberg, Joan; Ellison, Luke; Ghebremariam, Tewdros; Hung, Tien-Chieh; May, Bernie
Abstract: Genetic adaptation to captivity is a concern for threatened and endangered species held in conservation hatcheries. Here, we present evidence of genetic adaptation to captivity in a conservation hatchery for the endangered delta smelt (Fish Conservation and Culture Laboratory, University of California Davis; FCCL). The FCCL population is genetically managed with parentage analysis and the addition of wild fish each year. Molecular monitoring indicates little loss of genetic variation and low differentiation between the wild and conservation populations. Yet, we found an increase in offspring survival to reproductive maturity during the subsequent spawning season (recovery rate) in crosses that included one or both cultured parents. Crosses with higher levels of hatchery ancestry tend to produce a greater number of offspring that are recovered the following year. The recovery rate of a cross decreases when offspring are raised in a tank with fish of high levels of hatchery ancestry. We suggest changes in fish rearing practices at the FCCL to reduce genetic adaptation to captivity, as delta smelt numbers in the wild continue to decline and the use of FCCL fish for reintroduction becomes more likely.